2022
DOI: 10.1186/s12915-022-01428-7
|View full text |Cite
|
Sign up to set email alerts
|

Attention to visual motion suppresses neuronal and behavioral sensitivity in nearby feature space

Abstract: Background Feature-based attention prioritizes the processing of the attended feature while strongly suppressing the processing of nearby ones. This creates a non-linearity or “attentional suppressive surround” predicted by the Selective Tuning model of visual attention. However, previously reported effects of feature-based attention on neuronal responses are linear, e.g., feature-similarity gain. Here, we investigated this apparent contradiction by neurophysiological and psychophysical approac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 72 publications
4
4
0
Order By: Relevance
“…For both, close distractors shifted saccade plans, but the effects of the distractor decreased through intermediate distances and then re-activated at farther distances. These findings provide evidence of a spatial suppressive surround in oculomotor planning as was predicted and found in visual processing by the Selective Tuning model of attention (Cutzu and Tsotsos, 2003; Hopf et al, 2006; Kehoe et al, 2018b; Yoo et al, 2022). When the distractor was close to the target (AD = 1, 2) it was in the attentional window of the target and less suppression was induced.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…For both, close distractors shifted saccade plans, but the effects of the distractor decreased through intermediate distances and then re-activated at farther distances. These findings provide evidence of a spatial suppressive surround in oculomotor planning as was predicted and found in visual processing by the Selective Tuning model of attention (Cutzu and Tsotsos, 2003; Hopf et al, 2006; Kehoe et al, 2018b; Yoo et al, 2022). When the distractor was close to the target (AD = 1, 2) it was in the attentional window of the target and less suppression was induced.…”
Section: Discussionsupporting
confidence: 75%
“…The copyright holder for this preprint this version posted November 4, 2022. ; https://doi.org/10.1101/2022.11.03.514759 doi: bioRxiv preprint model of attention (Cutzu and Tsotsos, 2003;Hopf et al, 2006;Kehoe et al, 2018b;Yoo et al, 2022). When the distractor was close to the target (AD = 1, 2) it was in the attentional window of the target and less suppression was induced.…”
Section: Effects Of Angular Distance On Saccade Trajectoriesmentioning
confidence: 99%
“…Specifically, our observed task-dependent effects in early retinotopic areas are consistent with the literature on feature-based attention, which has shown that directing attention to simple visual features can modulate representations in early visual cortex (X. Chen et al, 2012; Foster & Ling, 2022; Gundlach et al, 2023; Jehee et al, 2011; Liu et al, 2003, 2007; Martinez-Trujillo & Treue, 2004; Mirabella et al, 2007; Saenz & Boynton, 2003; Serences & Boynton, 2007; Treue & Maunsell, 1996, 1999; Yoo et al, 2022). By modulating neurons coding for perceptual features that differentiate between categories, feature-based attention could provide a mechanism for improving the separability of different stimulus categories (Navalpakkam & Itti, 2007; Scolari et al, 2012; Scolari & Serences, 2009).…”
Section: Discussionsupporting
confidence: 90%
“…For example, computational models propose that feature-based attention (similar to spatial attention) operates via center-surround selection in feature space, allowing for isolation of the target from nearby distractor features 35,36 . These predictions have been supported by behavioral and electrophysiological findings that feature representations similar to the attended feature (i.e., nearby in feature space) are suppressed relative to more distant features 13,[37][38][39][40] . Other studies suggest that feature tuning can be sharpened around the focus of attention 41,42 , or that additional neural populations are recruited to allocate additional resources towards the selected feature (i.e., receptive field recruitment) [43][44][45][46] .…”
Section: Discussionmentioning
confidence: 79%